2022
DOI: 10.1007/s11356-021-18301-9
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic pollution in urban Lake Phewa, Nepal: the first report on abundance and composition in surface water of lake in different seasons

Abstract: Microplastics are man-made pollutants which have been detected in surface water and groundwater. Research on microplastic concentration in aquatic environment is attracting scientists from developing countries, but in Nepal no information regarding microplastic in freshwater system is available. Therefore, this study investigates the presence and abundance of microplastic in lake surface water of Phewa Lake, the second largest lake in Nepal. The average concentration of microplastic for surface water was 2.96 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Similarly, site L8 is also found to have a high abundance of microplastics (100 items/kg dw). The obstructing structure like the dam (Di & Wang, 2018 ), the long narrow topography at this section of the lake (Yuan et al, 2019 ), and the drainage of domestic wastewater and runoff by Phikre Khola (stream) near this site may be the factors for higher microplastic abundance in the lake at this region (Malla-Pradhan et al, 2022 ). Another probable source of microplastics at the outlet (Site L8) during the rainy season may be runoff from urban ditches.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, site L8 is also found to have a high abundance of microplastics (100 items/kg dw). The obstructing structure like the dam (Di & Wang, 2018 ), the long narrow topography at this section of the lake (Yuan et al, 2019 ), and the drainage of domestic wastewater and runoff by Phikre Khola (stream) near this site may be the factors for higher microplastic abundance in the lake at this region (Malla-Pradhan et al, 2022 ). Another probable source of microplastics at the outlet (Site L8) during the rainy season may be runoff from urban ditches.…”
Section: Resultsmentioning
confidence: 99%
“…Although many comprehensive studies on marine habitat are conducted, less research has concentrated on the freshwater ecosystem, which are possible sources and channels for the transport of microplastic into the marine habitat (Migwi et al, 2020 ). Although in recent years, there is a rise in microplastic pollution studies in worldwide lakes (Dusaucy et al, 2021 ), Nepal is at an early phase where only a limited research on microplastic has been done (Malla-Pradhan et al, 2022 ). Therefore, in order to address poorly quantified levels of microplastic pollution in the freshwater environment of Nepal, it is necessary to study the lakes to find the level of pollution from microplastics.…”
Section: Introductionmentioning
confidence: 99%
“…Among the review studies Lake Kallavesi of Finland was found to have the lowest microplastic concentration of 0.27 items/m 3 [47]. Oni et al [49] studied Ox-Bow Lake in Nigeria for 2 seasons and found the level of microplastic higher in dry season than raining season which was also the case of Phewa Lake, Nepal [71] (Table 4)…”
Section: Microplastic Abundance In Lake Watermentioning
confidence: 92%
“…Abundance (particle/m 3 ) Yuejin Lake, China [8] Urban Reservoir, China [9] Urban Waters, Megacity China [19] Phewa Lake, Nepal [20] Stormwater, Greater Paris [21] Langat River, Malaysia [22] Urban Lagoon, Tunisia [23] 7050 (mean) 28.3 (mean) 4000 (max) 28.3 (mean) 2.96 (mean) 129 (max) 453 (mean) Foam, followed by sheet types, was the dominant low-density microplastic morphology observed in these studied lakes (Figures 2a, b). Lake Pluit had the highest percentage of foam accounting for >80% of all identified microplastics, while Cipondoh and Gede had more percentages of the sheet as high as 40% of all detected microplastics (Figure 2c).…”
Section: Urban Watersmentioning
confidence: 99%